Implementation of RevoU Tech Academy's Independent Campus Program to Increase Digital Talent Capacity - Astriyani, Erna; Cholisoh, Novi; Amalia, Andiena; Syaputra, Harian (UNIVERSITAS RAHARJA, 2025)
The Merdeka Belajar Kampus Merdeka (MBKM) program aims to enrich students' hard and soft skills, preparing them better for the ever-changing challenges of the times. One of the independent study programs is RevoU Tech Academy